Managing quality of life in tourism and hospitality - Uysal, Muzaffer; Sirgy, M. Joseph, 1952-; Krüger, Stefan (CABI, 2018)
This book shares the work of various scholars under the umbrella of quality of life in tourism and hospitality, including case studies showing best practice. The main goal of this volume is to provide a portfolio of selected activities from tourism and hospitality settings as best practices and examine how these best practices play a role in the well-being of various stakeholder groups, including tourists, residents of the host community, and the providers of tourism services. The book has 11 chapters and a subject index.